KEPEMIMPINAN TRANSFORMASIONAL KYAI DALAM PENGEMBANGAN PESANTREN DI ERA DIGITAL: STUDI DI PONDOK PESANTREN MAMBAUS SHOLIHIN GRESIK - Syihabuddin, Muhammad Arif (Universitas Kiai Abdullah Faqih Gresik, 2024)
Abstrak: This research aims to explore the strategy and impact of Kyai's transformational leadership on the development of Mambaus Sholihin Islamic Boarding School in the digital era. The research method used is a qualitative approach with a case study at the Mambaus Sholihin Gresik Islamic Boarding School. Data were collected through in-depth interviews, participatory observation, and analysis of related documents. The results showed that Kyai at Mambaus Sholihin Gresik Islamic Boarding School implemented transformational leadership by combining traditional values with modern concepts. This strategy involves the application of information technology in religious learning, pesantren management, and internal communication. The positive impact of Kyai's transformational leadership can be seen in improving the quality of education, the involvement of students in digital learning, and the use of social media to spread the values of pesantren. This research contributes to the understanding of how Kyai's transformational leadership can steer pesantren towards positive adaptation to the development of digital technology. The practical implications of this research can be used as a guide for other pesantren institutions who want to update their approach in facing the challenges of the times. Kata Kunci: Transformational Leadership, Pesantren Development, Digital era.